2005
DOI: 10.1007/s10499-005-9018-x
|View full text |Cite
|
Sign up to set email alerts
|

Does overfeeding affect tench Tinca tinca (L.) juveniles?

Abstract: Duplicate groups of tench (Tinca tinca) juveniles (mean weight 0.69 g) were fed at 28°C for 70 days either a commercial formulated diet, Futura, or frozen Chironomidae larvae at four levels: below satiation, at about satiation, above satiation and well above satiation. These are represented by the feeding groups F1-F4 and C1-C4, respectively. No mortality was observed throughout the experiment. In groups F2-F4 a considerable incidence of uneaten food (>40% observations), deformities of the caudal penduncle, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 10 publications
5
55
1
Order By: Relevance
“…Vågsholm and Djupvik (1999) found that body deformities developed in Atlantic salmon (Salmo salar L.) more often in fast-growing fish than in slower-growing fish. A similar phenomenon was observed in juvenile tench (Rennert et al 2003, Kamler et al 2006). High growth rates require a disproportionate investment in P-rich biosynthetic cellular structures (Woods et al 2003).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Vågsholm and Djupvik (1999) found that body deformities developed in Atlantic salmon (Salmo salar L.) more often in fast-growing fish than in slower-growing fish. A similar phenomenon was observed in juvenile tench (Rennert et al 2003, Kamler et al 2006). High growth rates require a disproportionate investment in P-rich biosynthetic cellular structures (Woods et al 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Recently, the tendency of intensive aquaculture to produce fish of low biological quality, including those with body deformities, has become a problem of major importance (Witten et al 2009, Boglione et al 2013a, 2013b. In tench, an increasingly important aquaculture species, this problem is very common (Rennert et al 2003, Kamler et al 2006, Celada et al 2009, García et al 2010, González-Rodríguez et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Tench (Tinca tinca (L.)), is one such species, and although it has been cultured in polyculture with carp (Cyprinus carpio L.) for decades (e.g., Steffens 1995), interest in its culture in recirculating aquaculture systems (RAS) has been on the rise in recent years (Quirós et al 2003, Kamler et al 2006, Wang et al 2006, Zakêoe et al 2006). This species does not assimilate formulated feed very effectively, which can even result in significant losses during culture in RAS (Quirós et al 2003, Rennert et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The tench, Tinca tinca (Linnaeus, 1758), a freshwater fish belonging to the family Cyprinidae, has a great potential for aquaculture (Steffens 1995;Kamler et al 2006;Wang et al 2006;Wolnicki et al 2006). Originally occurring in the waters of Europe and Siberia, today tench occurs in the inland waters of all the continents (Skrzypczak and Mamcarz 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, feeding tench on commercial dry diets as the only food has been shown to reduce their growth exceptionally (Quirós and Alvariño 1998;Wolnicki and Myszkowski 1998;Quirós et al 2003) and increase the incidence of external body deformities (Rennert et al 2003;Wolnicki et al 2006;Kamler et al 2006), probably a response to unsuitable food. According to Quirós and Alvariño (1998) and Quirós et al (2003), survival and growth of tench can be improved by adding a supplement of live feed (Daphnia sp.…”
Section: Introductionmentioning
confidence: 99%